2015
DOI: 10.1101/gad.266098.115
|View full text |Cite
|
Sign up to set email alerts
|

p53 genes function to restrain mobile elements

Abstract: Throughout the animal kingdom, p53 genes govern stress response networks by specifying adaptive transcriptional responses. The human member of this gene family is mutated in most cancers, but precisely how p53 functions to mediate tumor suppression is not well understood. Using Drosophila and zebrafish models, we show that p53 restricts retrotransposon activity and genetically interacts with components of the piRNA (piwi-interacting RNA) pathway. Furthermore, transposon eruptions occurring in the p53 − germlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
179
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(195 citation statements)
references
References 62 publications
14
179
1
1
Order By: Relevance
“…To our knowledge, this is the first report of endogenous L1 mobilization being observed directly in a nonhuman cancer, with the possible exception of an L1 mutation found proximal to MYC in canine transmissible venereal tumors and arising either in the dog germline or the somatic evolution of the original tumor (Murgia et al 2006). Combined with a previous report of L1 and IAP protein expression in tumors obtained from a Myc murine liver cancer model (Wylie et al 2016), our results highlight mouse as a suitable system to study L1 activity in oncogenesis and cancer progression, which may be useful for future studies that are not feasible using human patient samples. Indeed, the finding that Mdr2 −/− mice accommodate tumor-specific L1 retrotransposition is particularly interesting, as these genomic alterations occur alongside massive gene amplifications (Iannelli et al 2014).…”
Section: Discussionsupporting
confidence: 62%
“…To our knowledge, this is the first report of endogenous L1 mobilization being observed directly in a nonhuman cancer, with the possible exception of an L1 mutation found proximal to MYC in canine transmissible venereal tumors and arising either in the dog germline or the somatic evolution of the original tumor (Murgia et al 2006). Combined with a previous report of L1 and IAP protein expression in tumors obtained from a Myc murine liver cancer model (Wylie et al 2016), our results highlight mouse as a suitable system to study L1 activity in oncogenesis and cancer progression, which may be useful for future studies that are not feasible using human patient samples. Indeed, the finding that Mdr2 −/− mice accommodate tumor-specific L1 retrotransposition is particularly interesting, as these genomic alterations occur alongside massive gene amplifications (Iannelli et al 2014).…”
Section: Discussionsupporting
confidence: 62%
“…Recently, a variety of repeat RNAs have been shown to activate the innate immune response through the pattern recognition receptor pathways (8,9,14,15). The expression of these repeats appears to be a combination of p53 function and DNA CpG methylation in model organisms (14,16). Our results have defined these Node, lymph node metastasis; +/-, node with or without metastasis.…”
Section: Discussionmentioning
confidence: 79%
“…However, recent evidence demonstrates that the association between p53 mutation and retrotransposon expression is more than simply a culling effect: indeed, p53 binding to target sites within LINE elements and other transposon sequences are associated with their downregulation (Chang et al, 2007). p53-mediated repression is dependent on epigenetic silencing of retrotransposon loci and not apoptosis, and derepressed retrotransposons are competent for reintegration into the genome (Leonova et al, 2013; Wylie et al, 2016), promoting mutagenesis (Tubio et al, 2014). Genomic analyses have revealed that retrotransposon mobilization is common in human cancers (Ting et al, 2011; Tubio et al, 2014).…”
Section: Revisiting the Guardian Of The Genomementioning
confidence: 99%
“…Genomic analyses have revealed that retrotransposon mobilization is common in human cancers (Ting et al, 2011; Tubio et al, 2014). While the precise impact remains to be determined, there is a significant association between repetitive element expression and p53 status in mouse and human tumors (Wylie et al., 2016). …”
Section: Revisiting the Guardian Of The Genomementioning
confidence: 99%